Challenges for establishing a learning support centre in rural areas for students with specific learning disorders. (c2016) - Daoud, Rania N. (2016)
Students with specific learning disorders (SLDs) who live in rural areas in Lebanon may be deprived of support programs that are based on expert assessment; consequently, their education may be compromised. This study provides a design for an out-of-school Center whose mission is to improve learning outcomes and decrease failure rate in the K-12 mainstream classrooms for students with SLDs. It provides support for such students with daily homework in reading, mathematics, and/or writing and with remediation and reinforcement during summer holidays. The Center‟s programs and strategies are derived from the relevant international and local literature and results of research conducted in a Lebanese rural area at a school that claims to have inclusive settings and cater for students with SLDs. Purposive sampling was used to identify the research site, students, their parents and teachers. Questionnaires were administered to students and teachers, and semi-structured interviews were conducted with the Principal, parents, Head of the special education department, and an expert in special education. The researcher‟s journal of a relevant experience and the reviewed literature served as bases for devising items for the various instruments which were piloted to ensure credibility. Qualitative data analysis and simple frequency counts yielded results that informed the design, programs, and handbook of the Center. The handbook includes definitions and description of SLDs, symptoms, assessment / diagnosis, and interventions as well as qualifications